Retained products of conception: What is the risk for recurrence on subsequent pregnancies?. (May 2018) - Smorgick, Noam; Mittler, Avital; Ben-Ami, Ido; Maymon, Ron; Vaknin, Zvi; Pansky, Moty
Abstract: Objective: To investigate whether women who were surgically treated for retained products of conception (RPOC) by either suction curettage or hysteroscopy are at risk for recurrent RPOC on their subsequent pregnancies. Study design: Retrospective analysis of 442 women surgically treated for RPOC following delivery or abortion by suction curettage (N = 63, 14.3%) or hysteroscopy (N = 379, 85.7%). Information on subsequent pregnancies and their outcomes was available for 161 (36.4%) women. Results: One or more live births were reported for 150 (93.2%) of the women for whom information on subsequent pregnancies was available. The overall rate of spontaneous abortions was 31/161 (19.3%). Recurrent RPOC were diagnosed in 25 (15.5%) cases, while third stage of labor placental problems (including retained placenta or cotyledons and placenta accreta) were found in 44 (27.3%) cases. Recurrent RPOC was associated with treatment by suction curettage compared with hysteroscopy for the initial RPOC on multivariate logistic regression analysis (Odds Ratio [OR] = 3.6, 95% Confidence Interval [CI]1.3–10.5, p = 0.01) and with the initial RPOC occurring after delivery compared with after abortion (OR = 8.4, 95%CI 1.8–39.5, p = 0.006). Conclusion: Women treated for RPOC are at risk for recurrent RPOC and for third stage of labor placental problems on their subsequent pregnancies, especially those who had been managed by suction curettage in comparison with operative hysteroscopy. Clinical and ultrasound follow-up in the early and late postpartum period should be considered in women with a history of RPOC.